Community Behavior in Family Planning with Contraceptive Method in Slum, Densely, and Poor Populated Areas in Jakarta - Simanjuntak, Menara; Sarjono, Haryadi (Humaniora, 2016)
The aim of this research was to measure whether there was a relationship of knowledge, feelings or affection, and behavior towards family planning with Long Term Contraceptive Method (LTCM) and the practice of Family Planning and Small Family Happy Prosperous Norm (SFHPN).The method used in this research was the quantitative approach with 1501 respondents that comprised of Eligible Couple that aged 15-49 years. The findings of this study are as many as 62,9% respondents use modern contraceptives, and 39,7% from the total of participants use LTCM. Then 75% of respondents want to use LTCM in the future. Family Planning Behavior has the significant relation to Family Planning Attitude. Considerable influence attitude towards practice SFHPN is low. Likewise, attitude towards practice LTCM is still low, and the attitude towards LTCM to practice SFHPN is also still low. The recommendations need to increase of communication, information, and education to Eligible Couples (Elco) on feeling safe and comfortable to use contraception LTCM. Recommendation from analysis and result is expected to be input into strategies and policies on education related to the cultivation of the National Family Planning program in Jakarta.